2017
DOI: 10.1111/febs.14309
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose acts as a uridine 5′‐diphosphoglucose‐competitive inhibitor of trehalose 6‐phosphate synthase in Corynebacterium glutamicum

Abstract: Trehalose is a compatible solute widely distributed in nature. The most prevalent pathway for its synthesis starts from condensation of glucose 6-phosphate (Glc6P) and uridine 5'-diphosphoglucose (UDP-Glc) catalyzed by trehalose 6-phosphate synthase (TPS). A previous laboratory evolution experiment with the bacterium Corynebacterium glutamicum generated strains adapted to supraoptimal temperatures, and the R328H substitution of the TPS encoded by otsA was shown to be associated with thermotolerance acquired by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…The protection might be accomplished by protecting cellular proteins from harmful oxidative attack, as trehalose has been proposed to protect proteins by physicochemical interactions with proteins [37]. Oide and Inui (2017) also recognized the importance of intracellular trehalose accumulation in cells in conferring heat resistance [38]. Furthermore, we found that otsB constitutes an operon with upstream genes NCgl2534 (hypothetical protein), otsA and NCgl2536 (membrane protein), and Pfeifer-Sancar et al also identified these genes as a sub-operon of a longer transcript that includes NCgl2533 ( thrE ) [36].…”
Section: Discussionmentioning
confidence: 99%
“…The protection might be accomplished by protecting cellular proteins from harmful oxidative attack, as trehalose has been proposed to protect proteins by physicochemical interactions with proteins [37]. Oide and Inui (2017) also recognized the importance of intracellular trehalose accumulation in cells in conferring heat resistance [38]. Furthermore, we found that otsB constitutes an operon with upstream genes NCgl2534 (hypothetical protein), otsA and NCgl2536 (membrane protein), and Pfeifer-Sancar et al also identified these genes as a sub-operon of a longer transcript that includes NCgl2533 ( thrE ) [36].…”
Section: Discussionmentioning
confidence: 99%
“…8). The steP mutants, AD-G, Wild-G, and Wild ΔsteP, are also expected to acquire (partial) thermotolerance by changing the metabolic flux to the PPP: increasing the metabolic flux via G6P to the PPP, probably because of feedback inhibition of OtsA, with trehalose accumulating inside the cells, as seen in other organisms (52,53). In addition, because the steP mutants were found to have some defect in sorbose assimilation, sorbitol seems to be directly utilized instead of sorbose in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose is a nonreducing disaccharide composed of two glucose units linked via an α-α-1,1-glycosidic bond. It is present in various invertebrates such as fungi, bacteria, plants, nematodes, and insects. Trehalase (TRE), a glucosidase, is the only enzyme that irreversibly hydrolyzes trehalose into two glucose molecules. There are two different forms of TRE in insects: soluble trehalase (TRE1) and membrane-bound trehalase (TRE2), which work in concert to maintain the insect’s energy supply.…”
Section: Introductionmentioning
confidence: 99%